Rice OsBRCA2 Is Required for DNA Double-Strand Break Repair in Meiotic Cells - Fu, Ruifeng; Wang, Chong; Shen, Hongyu; Zhang, Jie; Higgins, James D.; Liang, Wanqi (Frontiers in Plant Science, 2020)
The mammalian BREAST CANCER 2 (BRCA2) gene is a tumour suppressor that plays a crucial role in DNA repair and homologous recombination. Here we report the identification and characterization of OsBRCA2, the rice orthologue of human BRCA2. Osbrca2 mutant plants exhibit normal vegetative growth, but experience complete male and female sterility as a consequence of severe meiotic defects. Pairing, synapsis and recombination are impaired in osbrca2 male meiocytes, leading to chromosome entanglements and fragmentation. In the absence of OsBRCA2, localization to the meiotic chromosome axes of the strand-invasion proteins OsRAD51 and OsDMC1 is severely reduced and in vitro OsBRCA2 directly interacts with OsRAD51 and OsDMC1. These results indicate that OsBRCA2 is essential for facilitating the loading of OsRAD51 and OsDMC1 onto resected ends of programmed double-strand breaks (DSB) during meiosis to promote single-end invasions of homologous chromosomes and accurate recombination. In addition, treatment of osbrca2-1 seedlings with mitomycin C (MMC) led to hypersensitivity. As MMC is a genotoxic agent that creates DNA lesions in somatic cells that can only be repaired by homologous recombination these results suggest that OsBRCA2 has a conserved role in DSB repair and homologous recombination in rice.